Proximity-Based Asynchronous Messaging Platform for Location-Based Internet of Things Service - Hyeong gon Jo; Tae Yong Son; Seol Young Jeong; Soon Ju Kang (ISPRS International Journal of Geo-Information, 2016)
The Internet of Things (IoT) opens up tremendous opportunities to provide location-based applications. However, despite the services around a user being physically adjacent, common IoT platforms use a centralized structure, like a cloud-computing architecture, which transfers large amounts of data to a central server. This raises problems, such as traffic concentration, long service latency, and high communication cost. In this paper, we propose a physical distance-based asynchronous messaging platform that specializes in processing personalized data and location-based messages. The proposed system disperses traffic using a location-based message-delivery protocol, and has high stability.